ASUHAN KEPERAWATAN GANGGUAN MOBILITAS FISIK PADA NY.K DENGAN STROKE HEMORAGIK DI RUANG DEIKEA ROUJINHOME IKEDAEN OKINAWA JEPANG - Farhatun Nisa; Tri Sumarni; Suci Khasanah (Peneliti.net, 2026)
Hemorrhagic stroke is a leading cause of disability that often results in impaired physicalmobility. This case study aims to describe nursing care for Mrs. K (63 years old) with a diagnosis of hemorrhagic stroke in the Deikea Roujinhome Ikedaen Ward, Okinawa, Japan. The primary focus of this study is to address physical mobility barriers caused by left-sidedweakness (hemiparesis) with muscle strength scores of 1 for the upper extremity and 2 for thelower extremity. The method used is descriptive with a nursing process approach includingassessment to evaluation over three days. The primary nursing diagnosis established isimpaired physical mobility related to neuromuscular disorders. Interventions providedinclude passive and active Range of Motion (ROM) exercises, ambulation support using a wheelchair, and monitoring vital signs. Evaluation results showed a slight increase in functional ability, characterized by reduced pain and minimal ability to use left-hand exercisetools. In conclusion, providing regular ROM exercises and mobilization support provedbeneficial in maintaining joint flexibility and preventing further complications in post-stroke patients.